Anionic redox reaction and structural evolution of Ni-rich layered oxide cathode material. (July 2022) - Li, Shuwei; Liu, Zepeng; Yang, Lu; Shen, Xi; Liu, Qiuyan; Hu, Zhiwei; Kong, Qingyu; Ma, Jun; Li, Jiedong; Lin, Hong-Ji; Chen, Chien-Te; Wang, Xuefeng; et al.
Abstract: The Ni-rich layer-structured oxide is one of the most promising candidate cathode materials for the high energy-density Li-ion batteries. However, the commercial applications of these materials are hindered with drawbacks such as structural instability and poor cycling performance at high potentials. Herein, we comprehensively studied the oxygen redox reaction and the structural reversibility of LiNi0.83 Co0.12 Mn0.05 O2 at deep delithiation using the synchrotron X-ray absorption spectroscopy, scanning transmission electron microscopy and density functional theory calculations. The oxygen redox occurs due to the cation mixing upon delithiation in this material though there are no Li-O-Li configurations in its pristine form. The formation of the I 41 structure was attributed to the migration of the transition metals in the deeply delithiated material, extending the route of the phase transformation from the layered to the rock-salt structure. These findings are helpful to enrich the understanding of the origin of the oxygen redox and reveal its impact on the structural transformations in the Ni-rich layered oxides. These will spur new strategies to enhance the performance of the cathode materials for the next-generation Li-ion batteries. Graphical Abstract: ga1 Highlights: Oxygen redox can occur in the LiNi0.83 Co0.12 Mn0.05 O2 without Li-O-Li configurations at deep delithiation. The partially reversible I 41 structure are formed near the surface in the deeply delithiated material. Oxygen redox is coupled with the cation mixing.